1998
DOI: 10.1007/s002619900324
|View full text |Cite
|
Sign up to set email alerts
|

Renal squamous cell carcinoma: CT findings and clinical significance

Abstract: The central and peripheral types of RSCC were different biologically. High index of suspicion should be maintained when identifying the subtle clues of malignancy in patients with urolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 12 publications
0
63
0
2
Order By: Relevance
“…Significantly, due to nonspecific and insidious presenting symptoms, lack of specific radiological features, and rarity of this tumour, most cases of RSCC are undiagnosed preoperatively and diagnosis is only made by histopathological examination of the operated nephrectomy specimen. 3,4 Insidious onset of the disease, lack of any pathognomic sign or symptom and nonspecific findings on imaging leads to delay in diagnosis. Hence, most of the patients present with advanced disease, accounting for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, due to nonspecific and insidious presenting symptoms, lack of specific radiological features, and rarity of this tumour, most cases of RSCC are undiagnosed preoperatively and diagnosis is only made by histopathological examination of the operated nephrectomy specimen. 3,4 Insidious onset of the disease, lack of any pathognomic sign or symptom and nonspecific findings on imaging leads to delay in diagnosis. Hence, most of the patients present with advanced disease, accounting for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Squamous cell carcinoma of the urinary tract is more frequently reported in urinary bladder and male urethra and rarely encounterd in renal pelvis. [3][4][5][6] The involvement is unilateral, equally common on the right and left sides. Tumour may present as loin pain, hematuria, abdominal lump or with anorexia and weight loss in advanced cases.…”
Section: Discussionmentioning
confidence: 99%
“…This rare malignancy is frequently associated with chronic pyelonephritis and renal stone formation. Other etiologic factors such as tuberculosis, immunosuppression with azathioprine, analgesic abuse with phenacetin, radiation therapy, chronic rejection in a transplant kidney and prior percutaneous nephrolithotomy have been associated with squamous cell carcinoma [4][5][6][7]. It is believed that chronic irritation leads to squamous metaplasia which may subsequently develop into squamous cell carcinoma [8].…”
mentioning
confidence: 96%
“…[10,11] Nativ et al in their study divided renal SCC in three groups, reported 1 and 2 year survival rates of locally invasive renal SCC 33% and 22% respectively. [11] Metastatic disease survey is more shorter with reported median survival of 5 months.…”
Section: Dıscussıonmentioning
confidence: 99%